2020
DOI: 10.1029/2020gl087491
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne Middle‐ and Far‐Infrared Observations Improving Nighttime Ice Cloud Property Retrievals

Abstract: Two upcoming missions are scheduled to provide novel spaceborne observations of upwelling far-infrared spectra. In this study, the accuracy of ice cloud property retrievals using spaceborne middle-to-far-infrared (MIR-FIR) measurements is examined toward a better understanding of retrieval biases and uncertainties. Theoretical sensitivity studies demonstrate that the MIR-FIR spectra are sensitive to ice cloud properties, thereby providing a robust means for retrieving cloud properties under nighttime condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The wavelength-dependent LBLRTM-derived layer optical depths were then passed to LBLDIS, which takes scattering by particles in the cloud layer into account via the Discrete Ordinate Radiative Transfer (DISORT) code (Stamnes et al, 2000). In this study, the bulk optical properties used to simulate cloudy radiances were those provided by Baum et al (2014) using 16 streams.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The wavelength-dependent LBLRTM-derived layer optical depths were then passed to LBLDIS, which takes scattering by particles in the cloud layer into account via the Discrete Ordinate Radiative Transfer (DISORT) code (Stamnes et al, 2000). In this study, the bulk optical properties used to simulate cloudy radiances were those provided by Baum et al (2014) using 16 streams.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…It has been proven that the application of the Chou scheme results in a systematic overestimation of simulated nadir radiances at the TOA [33]. These discrepancies can be primarily attributed to the average quantities employed to approximate Equations ( 6) and (7), which are larger than their true values. To establish a more accurate computational scheme for upward radiances, it is essential to incorporate a more realistic representation of these two terms.…”
Section: The Radiative Transfer Equation and The Mama Approximationmentioning
confidence: 99%
“…Radiation fields at FIR wavelengths are also strongly influenced by the presence of clouds. In particular, recent studies have demonstrated the larger sensitivity of FIR radiance to scattering by ice particles with respect to the mid-infrared part of the spectrum [5][6][7]. Despite its significance, mostly due to technical difficulties, the FIR remains currently unobserved from space.…”
Section: Introductionmentioning
confidence: 99%
“…Early theoretical studies implied that measurements of the outgoing far‐IR spectrum should give unique information of crystal habit and size distribution (Yang et al., 2003). More recent work has demonstrated that measurements of ice cloud optical properties across the full IR range can improve the quantification of cloud optical thicknesses and effective sizes of ice clouds under nighttime conditions robustly when visible and near‐IR solar‐band measurements are unavailable (Saito et al., 2020). Nonetheless, work exploiting airborne observations of far‐IR radiances in the presence of cirrus clouds demonstrate an inability to simulate measurements consistently across the far‐IR and Mid‐IR spectrum using available ice‐cloud bulk optical property data sets (Bantges et al., 2020; Cox et al., 2010).…”
Section: Introductionmentioning
confidence: 99%